Factors affecting recombinant Western equine encephalitis virus glycoprotein production in the baculovirus system - Toth, Ann M. (2011)
In an effort to produce processed, soluble Western equine encephalitis virus (WEEV) glycoproteins for subunit therapeutic vaccine studies, we isolated twelve recombinant baculoviruses designed to express four different WEEV glycoprotein constructs under the transcriptional control of three temporally distinct baculovirus promoters. The WEEV glycoprotein constructs encoded full-length E1, the E1 ectodomain, an E26KE1 polyprotein precursor, and an artificial, secretable E2E1 chimera. The three different promoters induced gene expression during the immediate early (ie1), late (p6.9), and very late (polh) phases of baculovirus infection. Protein expression studies showed that the nature of the WEEV construct and the timing of expression both influenced the quantity and quality of recombinant glycoprotein produced. The full-length E1 product was insoluble, irrespective of the timing of expression. Each of the other three constructs yielded soluble products and, in these cases, the timing of expression was important, as higher protein processing efficiencies were generally obtained at earlier times of infection. However, immediate early expression did not yield detectable levels of every WEEV product, and expression during the late (p6.9) or very late (polh) phases of infection provided equal or higher amounts of processed, soluble product. Thus, while earlier foreign gene expression can provide higher recombinant glycoprotein processing efficiencies in the baculovirus system, in the case of the WEEV glycoproteins, earlier expression did not provide larger amounts of high quality, soluble recombinant glycoprotein product.